A Study of Demographic and Psychological Factors That Effect The Buying Behavior Of Rural, Semi Urban and Urban Telecom Users In And Around Chandigarh - sethi, upasna; Chawla, A.S. (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
People don't care how much you know until they know how much you care-about them and their problems-Robert Cavett Consumer behavior is the behavior of individuals to buy goods and services for personal consumption. According to black box model of consumer behavior, there are two main stimuli that effect the purchasing decision of a consumer i.e. Consumers buyers characteristics and consumers buying decisions. Indian Telecom sector is the fastest growing sector and its market is 2nd biggest market in the world after china. Due to entry of many competitors in the market after the liberalization and privatization of this sector the competition has become very stiff and so it is important for the marketers to understand the consumer behavior. This study is an attempt to find out the target audience and the different psychological factors that have influence on the customers of rural, semi urban and urban areas.